2014
DOI: 10.1162/jocn_a_00673
|View full text |Cite
|
Sign up to set email alerts
|

Early Anticipation Lies behind the Speed of Response in Conversation

Abstract: Abstract■ RTs in conversation, with average gaps of 200 msec and often less, beat standard RTs, despite the complexity of response and the lag in speech production (600 msec or more). This can only be achieved by anticipation of timing and content of turns in conversation, about which little is known. Using EEG and an experimental task with conversational stimuli, we show that estimation of turn durations are based on anticipating the way the turn would be completed. We found a neuronal correlate of turn-end a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 60 publications
9
94
0
Order By: Relevance
“…Predicting this point enables the listener to articulate their response at the appropriate moment, so the risk of extensive conversational overlap or a long gap is minimized. Most research assessing turn-end prediction has used a button-press paradigm (e.g., De Ruiter et al, 2006;Magyari et al, 2014), in which participants are presented with full conversational turns and predict (indicated via a button-press) when they expect speakers to reach the end of their utterance. Using this paradigm, De Ruiter et al found that participants could accurately predict when a speaker's turn was about to end.…”
Section: Predicting the Speaker's Turnmentioning
confidence: 99%
See 4 more Smart Citations
“…Predicting this point enables the listener to articulate their response at the appropriate moment, so the risk of extensive conversational overlap or a long gap is minimized. Most research assessing turn-end prediction has used a button-press paradigm (e.g., De Ruiter et al, 2006;Magyari et al, 2014), in which participants are presented with full conversational turns and predict (indicated via a button-press) when they expect speakers to reach the end of their utterance. Using this paradigm, De Ruiter et al found that participants could accurately predict when a speaker's turn was about to end.…”
Section: Predicting the Speaker's Turnmentioning
confidence: 99%
“…Further evidence for this conclusion comes from a study by Magyari et al (2014), who manipulated the content predictability of their stimuli. In a gating paradigm, participants were auditorily presented with turns from actual conversations in fragments of increasing duration and completed these turns with the words they expected to follow the preceding context (much like a typical cloze task; Taylor, 1953).…”
Section: Predicting the Speaker's Turnmentioning
confidence: 99%
See 3 more Smart Citations